Moderator effect of COVID-19 fear on "mediating role of boredom proneness in relationship between internet addiction and DASS-21" - Halim Guner (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - COVID-19 emerged at a time when many different psychological factors can negatively affect the human psychology, and thereby making life even more difficult over and above the physical health impact. As known, with the development of modern-day technology, Internet usage has become a part of everyday life. However, this situation often brings about the problem of Internet addiction. A positive relationship is known to exist between Internet addiction and psychological problems. This study aims to examine the moderator effect of COVID-19 fear on the "mediating role of boredom proneness in relationship between internet addiction and DASS-21." Materials/methods - In the current study, the effect of boredom proneness in this relationship was examined through the mediator effect of boredom proneness in the relationship between Internet addiction and the "Depression, stress and anxiety scale" DASS-21. Then, the moderator effect of the fear of COVID-19 was examined on the mediator role, which constitutes the main purpose of this research. For these purposes, 560 students studying at the undergraduate level at state universities in Turkey were reached as a sample. In the analysis of the collected data; parametric tests, correlation test, structural equation model, and moderator analysis were employed. Results - In the model in which the moderator effect of COVID-19 fear was examined; it appears that fear of COVID-19 increases the relationship between Internet addiction and boredom proneness. It also increases the relationship between boredom proneness and DASS-21. However, no significant moderator effect was found to exist in the relationship between Internet addiction and DASS-21. Conclusion - This study shows that the fear of COVID-19 has a significant effect on Internet addiction, boredom proneness, and psychological problems. This research was conducted based on the analysis of certain variables, presentation of the results and their subsequent discussion, and the putting forward of various suggestions.